CONSERVATION OF THE PASEMAH MEGALITHIC SITES IN THE MODERN ERA: CHALLENGES AND DIGITAL TECHNOLOGY-BASED PRESERVATION STRATEGIES - Susi Harnisa; Tama Maysuri; Siti Musa'adah; Rendy Wahyu Satrio Putro (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
The Pasemah megalithic site in South Sumatra is an invaluable cultural heritage reflecting the social, religious, and aesthetic life of prehistoric communities. However, its preservation faces serious challenges, including environmental degradation, land-use conversion, weak regulations, and limited public awareness of ancestral heritage. In the modern era, conservation efforts should not only focus on physical maintenance but also integrate digital technology as a strategic approach. Digitization through three-dimensional mapping, virtual reconstruction, online archives, and dissemination via digital media can expand public access and awareness. Such strategies not only safeguard the authenticity of the site but also promote it globally as an educational and cultural resource. Technology-based conservation requires synergy among government, academics, local communities, and the wider society to ensure the sustainability of its historical values for future generations.